Chemical composition of sedimentary organic carbon differs significantly between the intact and restored mangroves in the Philippines - R. Ray; M. Kida; R. Suwa; T. Miyajima; Charissa M. Ferrera; Rene Rollon; Yasmin H. Primavera-Tirol; Maria Lourdes San Diego-McGlone; Kazuo Nadaoka (Organic Geochemistry, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Hormone-optimized hypocotyl–epicotyl–cotyledonary tri-complex explant system enables efficient soybean transformation with reduced genotype dependence - J. Sushmitha; Durgeshwari Prabhakar Gadpayale; Navita Bansal; Ranjeet R. Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; Ashish Marathe; R. Dinesh Kumar; Akshay Talukdar; Giriraj Kumawat; Viswanathan Chinnusamy; et al. (Plant Cell Reports, 2026)

Influence of chickpea and barley semolina on durum wheat pasta: Milling, processing, and quality attributes - Bhavyatha G.; Amrita Ray; Sreechithra T. V.; Suresh D. Sakhare (Food and Humanity, 2026)

A case report of a pathology in the ‘whip’ of a flagellicaudatan sauropod - Tom T.P. van der Linden; D. Ray Wilhite; Gunnar T. Bivens; D. Cary Woodruff; Rick J. Hunter; Tim Stecko; Brian D. Curtice (The Science of Nature, 2026)
Flagellicaudatan sauropods are well known for their elongated tails which end in a ‘whiplash’-like structure, consisting of biconvex rod-like caudal vertebrae lacking a neural arch. A remarkably well-preserved and relatively complete specimen of Barosaurus from the Upper Jurassic Morrison Formation preserves a number of these vertebrae, including the last two that terminate the axial series. The penultimate element preserves a distinct callus which we investigated, together with the terminal caudal vertebra, using X-ray computed tomography. A transverse fracture initiated the formation of the callus, highlighted by extensive, disorganized vascularization of the bone outside of the cortex. Healing was likely still ongoing as the vertebra remains in two parts. Although various etiologies can be proposed for the trauma, none can be unambiguously put forward as the cause. The last caudal shows an interesting vascular pattern, and together with the lack of a posterior articular surface, can here be definitely identified as the last vertebra in the axial series. There is substantial variability in the morphology of the last caudal vertebra throughout Sauropoda, and future studies should focus on the soft tissues in this part of the tail, thereby enlightening the potential function of the ‘whip’. We also highlight here the use of high-resolution scanning to reveal the internal structures of fossils in detail when consumptive analysis is not possible.

Genome‐wide associations of leaf spectral variation in MAGIC lines of Nicotiana attenuata - Cheng Li; Ewa A. Czyż; Bernhard Schmid; Rishav Ray; Rayko Halitschke; Ian T. Baldwin; Michael E. Schaepman; Meredith C. Schuman (Ecology, 2026)
The application of in‐field and aerial spectroscopy to assess functional and phylogenetic variation in plants has led to novel ecological insights and supports global assessments of plant biodiversity. Understanding how plant genetic variation influences reflectance spectra will help harness this potential for biodiversity monitoring and improve understanding of why plants differ in functional responses to environmental change. Here, we use a well‐resolved genetic mapping population derived from Multiparent Advanced Generation Inter‐cross (MAGIC) lines of Nicotiana attenuata to associate genetic differences with differences in leaf spectra between plants in a field experiment in their natural environment. We analyzed the leaf reflectance spectra using a hand‐held spectroradiometer (350–2500 nm) on 616 fully genotyped plants of N. attenuata grown in a randomized block design. We tested three approaches to conducting genome‐wide association studies on spectral variants. We introduce a new hierarchical spectral clustering with parallel analysis (HSC‐PA) method. This method efficiently captured the variation in our high‐dimensional dataset and allowed us to discover a novel association, between a locus on chromosome 1 and the 734–1143 nm spectral range, spanning the red‐edge and near‐infrared regions that are sensitive to leaf structure and photosynthetic activity. This locus contains a candidate gene annotated as carbonic anhydrase, an enzyme involved in CO₂ hydration and regulation of photosynthetic efficiency, suggesting a physiological link between variation in leaf optical properties and carbon assimilation. In contrast, an approach treating single wavelengths as phenotypes identified genetic signals highly consistent with HSC‐PA, but suffered from massive statistical redundancy without pinpointing significant, interpretable features. An index‐based approach, which reduces complex spectra to a few dimensionless variables, detected two significant associations for (a water‐content‐related index) with loci on chromosome 1 near genes annotated as a Zeta toxin domain‐containing protein, and an Exocyst subunit Exo70 family protein. While these findings are biologically plausible, they represent a very narrow subset of the spectral variation captured by HSC‐PA. The HSC‐PA approach supports a comprehensive understanding of the genetic determinants of leaf spectral variation that is data‐driven but human‐interpretable and is thus a tool to discover genetic differences underlying intraspecific variation, a foundation of biodiversity.

Integration of smartphone imagery with topographic parameters for soil organic carbon prediction in the Indo-Gangetic Plains: an interpretable machine learning approach - Abhradip Sarkar; Pragati Pramanik Maity; Fitsum T. Teshome; V.K. Sehgal; Alka Arora; Md Ashraful Haque; Bappa Das; Mrinmoy Ray; Siddhartho Shekhar Paul (Computers and Electronics in Agriculture, 2026)

Evaluating the performance of selected CMIP6 GCMs for simulations of historical temperature over Ethiopia - Alehegn Belay Tagele; Temesgen Gashaw Tarkegn; Pieter R. van Oel; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Othoo Calvince Ouko; Daniel Berhanu; Amare Haileslassie; Abeyou W. Worqlul; Amare Bantider; et al. (Theoretical and Applied Climatology, 2026)
This study evaluates the performance of seven Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and their Ensemble mean in reproducing historical maximum (Tmax) and minimum (Tmin) temperatures across five agro-ecological zones (AEZs) of Ethiopia during 1995–2014. The assessment covers daily to annual time scales using observational and GCM datasets. Model performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), and correlation coefficient (r), while the Comprehensive Rating Index (CRI) was applied for ranking. Results show substantial spatial and temporal variability in model performance. For Tmax, the Ensemble mean and EC-Earth3-veg performed best at the daily scale, while EC-Earth3-veg, MPI-ESM1-2-LR and BCC-CSM2-MR excelled at the monthly scale across most AEZs. Seasonally, top-performing models included Ensemble mean, MPI-ESM1-2-LR and MRI-ESM2-0 during Bega (October-January), EC-Earth3-veg, CNRM-CM6-1 and Ensemble mean during Belg (February-May) and CNRM-CM6-1 and MPI-ESM1-2-LR during Kiremt (June-September). For Tmin, CNRM-CM6-1, BCC-CSM2-MR and Ensemble mean ranked highest at both daily and monthly scales in most AEZs. At the annual scale, MRI-ESM2-0, Ensemble mean, MPI-ESM1-2-LR and CNRM-CM6-1 excel for Tmax, while EC-Earth3-veg, BCC-CSM2-MR and Ensemble mean lead for Tmin across most AEZs. MIROC6 consistently exhibited the weakest performance for both Tmax and Tmin across most AEZs and time periods. Thus, the Ensemble mean of all evaluated models does not consistently rank among the top three performers across all AEZs and time scales. The identified best-performing CMIP6 models provide valuable tools for assessing climate change impacts and developing region-and time-specific adaptation strategies in Ethiopia. Given the variability in GCM performance across AEZs and time scales, national or large-scale studies would benefit from using the Ensemble mean derived from the best-performing models. This study provides crucial insights into the strengths and weaknesses of different GCMs, supporting evidence-based decision-making and enhancing efforts to build climate resilience and adaptation strategies in the region.

Correction: Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in Lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Letter to the Editor: Misclassification of fibres in Ramage et al. (2025) and implications for microplastics research - Kelly J. Sheridan; Richard S. Blackburn; Miranda T. Prendergast-Miller; Josephine Jones; Ray Palmer; Thomas Stanton (Chemosphere, 2025)

Petrology and Geochemistry of Poikilitic Shergottite Northwest Africa 1950: bridging the gap between depleted and intermediate sources in Martian Mantle - Varsha M Nair; Amit Basu Sarbadhikari; G N S Sree Bhuvan; T. Vijaya Kumar; Nilanjana Sorcar; Sneha Mukherjee; E.V.S.S.K. Babu; Jyotiranjan S. Ray (Geochimica et Cosmochimica Acta, 2025)

Optimized Agrobacterium-mediated CRISPR/Cas9 transformation in soybean through comparative evaluation of cotyledonary node and half-seed explants - Durgeshwari Prabhakar Gadpayale; J. Sushmita; Navita Bansal; Shalini Singh; Ch Prasanna Kumari; C. R. Nagesh; Ranjeet Ranjan Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; R. Dinesh Kumar; Arun Kumar; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Examining the impacts of spatial closures in the Gulf Menhaden fishery - Robert T. Leaf; Wei Wu; Ray M. Mroch; Robert Trigg; David Duval (Frontiers in Marine Science, 2025)
Policymakers in the northern Gulf of America have proposed various spatial closures in recent years as a management tool for the Gulf Menhaden Brevoortia patronus fishery. In this work, we aim to understand how the seasonal movement of the stock will impact the efficacy of spatial restrictions by examining the short-term impacts of simulated area closures of 1.6, 3.2, and 4.8 km adjacent to land on the commercial Gulf Menhaden fishery using commercial logbook data from 2006 to 2009 and 2011. We used bootstrap resampling (n = 1,000) of trip-level data to describe five descriptive metrics. These were the mean set-specific catch per unit effort (CPUE, metric tons, mt set -1 ), the mean number of sets deployed on each trip, the mean trip-specific CPUE (mt minute -1 ), the median distance (km) traveled to the first set, and the median distance (km) traveled among subsequent sets (for trips with at least two sets). We explored the impacts of closures by comparing the month-specific distributions of the descriptive metrics from all trips to those calculated using only those trips with all sets outside of a particular restricted area. Using the simulation, we evaluated the resulting spatial differences in fishing effort that would occur. The results of the simulation indicated that, in all restriction scenarios for all months, the spatial restrictions served to increase the travel distance to the first set and to reduce the mean number of sets taken. Set-specific and trip-specific CPUE are reduced in the restriction scenarios. We found that the reduction of total harvest (mt) for the 1.6 km restriction regime was 4.3 to 7.2%, 9.1 to 12.0% in the 3.2 km restriction regime, and 12.7 to 15.4% in the 4.8 km restriction regime. This work provides information about the impacts on the fishery that result from area closures. Such information is necessary to evaluate the efficacy and impacts of spatial closures for the Gulf Menhaden fishery.

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

In silico exploration of pyrocannabinoid interactions with key protein targets - Giovanni A. Ramirez; Tesfay T. Tesfatsion; Monica K. Pittiglio; Kyle P. Ray; Andrew Westerkamp; Westley Cruces (In Silico Pharmacology, 2025)

Performances of reanalysis products in representing the temperature climatology of Ethiopia - Tazebew Abera Tadesse; Temesgen Gashaw Tarkegn; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Abeyou W. Worqlul; Pieter R. van Oel; Yihun T. Dile; Abebe D. Chukalla; Amare Haileslassie; Endeg Aniley; et al. (Theoretical and Applied Climatology, 2025)

Ecology of arbuscular mycorrhizal association in coconut (Cocos nucifera L.) palms: Analysis of factors influencing AMF in fields - Sreejamol T. N; Joseph George Ray (Rhizosphere, 2024)

Trends in Arctic-nesting loon (Gavia spp.) populations in North America - Ingrid L. Pollet; Sarah E. Gutowsky; Ray T. Alisauskas; William Harvey; Dana K. Kellett; Kristen M. Lalla; Josée Lefebvre; Jake Russell-Mercier; Jennifer F. Provencher; Emily D. Silverman; Paul A. Smith; Mark L. Mallory (Polar Biology, 2024)

Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Fish on the platter! Dietary habits of fishing cats (Prionailurus viverrinus) in the Godavari Delta, India - Giridhar Malla; Paromita Ray; Yellapu Srinivas; Sudhakar Malla; T Byragi Reddy; Matt Hayward; Kuppusamy Sivakumar (Mammal Research, 2024)

Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

Identifying critical microbes in guayule-microbe and microbe-microbe associations - Yongjian Chen; David A. Dierig; Guangyao Wang; Diaa Eldin M. Elshikha; Dennis T. Ray; Albert Barberán; Raina M. Maier; Julia W. Neilson (Plant and Soil, 2024)

SoJel –A 3D printed jellyfish-like robot using soft materials for underwater applications - Pawandeep Singh Matharu; Zhong Wang; John H. Costello; Sean P. Colin; Ray H. Baughman; Yonas T. Tadesse (Ocean Engineering, 2023)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

On the occurrence of low concentration hyperpycnal river plumes in a small mountainous river-canyon system - Sheng-De Tsai; Yu-Chi Lin; Andhy Romdani; Jia-Lin Chen; Ray T. Hsu; James T. Liu (Continental Shelf Research, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

Variation in migration behaviors used by Arctic Terns (Sterna paradisaea) breeding across a wide latitudinal gradient - Joanna B. Wong; Simeon Lisovski; Ray T. Alisauskas; Willow English; Autumn-Lynn Harrison; Dana K. Kellett; Mark Maftei; Avery Nagy-MacArthur; Robert A. Ronconi; Paul A. Smith; Mark L. Mallory; Marie Auger-Méthé (Polar Biology, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Improving estimates of the state of global fisheries depends on better data - Daniel Ovando; Ray Hilborn; Cole Monnahan; Merrill Rudd; Rishi Sharma; James T. Thorson; Yannick Rousseau; Yimin Ye (Fish and Fisheries, 2021)
Implementation of the United Nations Sustainable Development Goals requires assessments of the global state of fish populations. While we have reliable estimates of stock status for fish populations accounting for approximately half of recent global catch, our knowledge of the state of the majority of the world's “unassessed” fish stocks remains highly uncertain. Numerous publications have produced estimates of the global status of these unassessed fisheries, but limited quantity and quality of data along with methodological differences have produced counterintuitive and conflicting results. Here, we show that despite numerous efforts, our understanding of the status of global fish stocks remains incomplete, even when new sources of broadly available data are added. Estimates of fish populations based primarily on catch histories on average performed 25% better than a random guess. But, on average, these methods assigned fisheries to the wrong FAO status category 57% of the time. Within these broad summaries, the performance of models trained on our tested data sources varied widely across regions. Substantial improvements to estimates of the state of the world's exploited fish populations depend more on expanded collection of new information and efficient use of existing data than development of new modelling methods.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Was historical cisco Coregonus artedi yield consistent with contemporary recruitment and abundance in Lake Superior? - Benjamin J. Rook; Michael J. Hansen; Cory A. Goldsworthy; Bradley A. Ray; Owen T. Gorman; Daniel L. Yule; Charles R. Bronte (Fisheries Management and Ecology, 2021)
Historically, cisco Coregonus artedi Lesueur was the predominant prey fish and target of commercial fisheries throughout Lake Superior, but most spawning stocks collapsed by the mid‐1900s. Stocks partially recovered by the early 1990s, but contemporary abundance is considered to be below historical levels and driven by intermittent recruitment. Stochastic, age‐structured simulation models were used to determine whether historical (pre‐1955) cisco yield in Lake Superior was consistent with contemporary (1992–2015) abundance, life‐history characteristics and recruitment dynamics. When compared to contemporary stocks, the findings suggest historical stocks had: (1) similar recruits per spawner at low spawning stock sizes; (2) lower rates of compensatory density dependence; (3) similar or lower recruitment variation depending on the area and (4) higher median adult and age‐1 density. These findings are consistent with the hypothesis that eutrophication during the historical period supported greater recruitment and adult abundance and that re‐oligotrophication during the contemporary period may be limiting full recovery.

Attempted Isolation of Cryptococcus Species and Incidental Isolation of Exophiala dermatitidis from Human Oral Cavities - Caroline P. Toberna; Jessica J. F. Kram; Eric T. Beck; Sommer Ray; Tyler Gavinski; Alana K. Sterkel; Dennis J. Baumgardner (Mycopathologia, 2020)

Stable quantitative trait locus (QTL) for sheath blight resistance from rice cultivar CR 1014 - Archana Bal; Pankajini Samal; Mridul Chakraborti; Arup Kumar Mukherjee; Soham Ray; Kutubuddin A. Molla; Lambodar Behera; Rashmita Samal; Sarmistha Sarangi; Pritiranjan Sahoo; Motilal Behera; Srikanta Lenka; et al. (Euphytica, 2020)

Stability prediction of Himalayan residual soil slope using artificial neural network - Arunava Ray; Vikash Kumar; Amit Kumar; Rajesh Rai; Manoj Khandelwal; T. N. Singh (Natural Hazards, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Bioaccumulation of vanadium (V), niobium (Nb) and tantalum (Ta) in diverse mangroves of the Indian Sundarbans - R. Ray; B. Dutta; S. K. Mandal; A. G. González; O. S. Pokrovsky; T. K. Jana (Plant and Soil, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Geophagy among East African Chimpanzees: consumed soils provide protection from plant secondary compounds and bioavailable iron - Paula A. Pebsworth; Stephen Hillier; Renate Wendler; Ray Glahn; Chieu Anh Kim Ta; John T. Arnason; Sera L. Young (Environmental Geochemistry and Health, 2019)

Water Column Effects on In Situ Spectral Signatures of Coral Species from Gujarat Coast, India - Nandini Ray Chaudhury; Ashwin Gujrati; T. V. R. Murthy (Journal of the Indian Society of Remote Sensing, 2019)

Cuff inflation time significantly affects blood flow recorded with venous occlusion plethysmography - Rehan T. Junejo; Clare J. Ray; Janice M. Marshall (European Journal of Applied Physiology, 2019)

Novel biotic stress responsive candidate gene based SSR (cgSSR) markers from rice - Kutubuddin Ali Molla; T. P. Muhammed Azharudheen; Soham Ray; Sutapa Sarkar; Alaka Swain; Mridul Chakraborti; Joshitha Vijayan; Onkar Nath Singh; Mirza Jaynul Baig; Arup Kumar Mukherjee (Euphytica, 2019)

Clotam enhances anti-proliferative effect of vincristine in Ewing sarcoma cells - Sagar Shelake; Umesh T. Sankpal; Don Eslin; W. Paul Bowman; Jerry W. Simecka; Sangram Raut; Anish Ray; Riyaz Basha (Apoptosis, 2019)

Biogenic hydrogen sulphide emissions and non-sea sulfate aerosols over the Indian Sundarban mangrove forest - D. Ganguly; R. Ray; N. Majumdar; C. Chowdhury; T. K. Jana (Journal of Atmospheric Chemistry, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Erratum: Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Genome-wide association mapping of canopy wilting in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; C. Andy King; Larry C. Purcell (Theoretical and Applied Genetics, 2017)

Human activity was a major driver of the mid‐Holocene vegetation change in southern Cumbria: implications for the elm decline in the British Isles - Mark J. Grosvenor; Richard T. Jones; Chris S. M. Turney; Dan J. Charman; Alan Hogg; Dave Coward; Ray Wilson (Journal of Quaternary Science, 2017)
The dramatic decline in elm ( Ulmus ) across a large swathe of north‐west Europe in the mid‐Holocene has been ascribed to a number of possible factors, including climate change, human activity and/or pathogens. A major limitation for identifying the underlying cause(s) has been the limited number of high‐resolution records with robust geochronological frameworks. Here, we report a multiproxy study of an upland (Blea Tarn) and lowland (Urswick Tarn) landscape in southern Cumbria (British Isles) to reconstruct vegetation change across the elm decline in an area with a rich and well‐dated archaeological record to disentangle different possible controls. Here we find a two‐stage decline in Ulmus taking place between 6350–6150 and 6050–5850 cal a BP, with the second phase coinciding with an intensification of human activity. The scale of the decline and associated human impact is more abrupt in the upland landscape. We consider it likely that a combination of human impact and disease drove the Ulmus decline within southern Cumbria.

Crustal deformation rates in Assam Valley, Shillong Plateau, Eastern Himalaya, and Indo-Burmese region from 11 years (2002–2013) of GPS measurements - Prakash Barman; Sridevi Jade; T. S. Shrungeshwara; Ashok Kumar; Sanjeev Bhattacharyya; Jagat Dwipendra Ray; Saigeetha Jagannathan; Wangshi Menla Jamir (International Journal of Earth Sciences, 2017)

Migratory stopover timing is predicted by breeding latitude, not habitat quality, in a long-distance migratory songbird - A. Van Loon; J. D. Ray; A. Savage; J. Mejeur; L. Moscar; M. Pearson; M. Pearman; G. T. Hvenegaard; N. Mickle; K. Applegate; K. C. Fraser (Journal of Ornithology, 2017)

Decadal declines in avian herbivore reproduction: density‐dependent nutrition and phenological mismatch in the Arctic - Megan V. Ross; Ray T. Alisauskas; David C. Douglas; Dana K. Kellett (Ecology, 2017)
A full understanding of population dynamics depends not only on estimation of mechanistic contributions of recruitment and survival, but also knowledge about the ecological processes that drive each of these vital rates. The process of recruitment in particular may be protracted over several years, and can depend on numerous ecological complexities until sexually mature adulthood is attained. We addressed long‐term declines (23 breeding seasons, 1992–2014) in the per capita production of young by both Ross's Geese ( Chen rossii ) and Lesser Snow Geese ( Chen caerulescens caerulescens ) nesting at Karrak Lake in Canada's central Arctic. During this period, there was a contemporaneous increase from 0.4 to 1.1 million adults nesting at this colony. We evaluated whether (1) density‐dependent nutritional deficiencies of pre‐breeding females or (2) phenological mismatch between peak gosling hatch and peak forage quality, inferred from NDVI on the brood‐rearing areas, may have been behind decadal declines in the per capita production of goslings. We found that, in years when pre‐breeding females arrived to the nesting grounds with diminished nutrient reserves, the proportional composition of young during brood‐rearing was reduced for both species. Furthermore, increased mismatch between peak gosling hatch and peak forage quality contributed additively to further declines in gosling production, in addition to declines caused by delayed nesting with associated subsequent negative effects on clutch size and nest success. The degree of mismatch increased over the course of our study because of advanced vegetation phenology without a corresponding advance in Goose nesting phenology. Vegetation phenology was significantly earlier in years with warm surface air temperatures measured in spring (i.e., 25 May–30 June). We suggest that both increased phenological mismatch and reduced nutritional condition of arriving females were behind declines in population‐level recruitment, leading to the recent attenuation in population growth of Snow Geese.

Evaluating species-specific changes in hydrologic regimes: an iterative approach for salmonids in the Greater Yellowstone Area (USA) - Robert Al-Chokhachy; Adam J. Sepulveda; Andrew M. Ray; David P. Thoma; Michael T. Tercek (Reviews in Fish Biology and Fisheries, 2017)

Conversion of tundra to exposed peat habitat by snow geese (Chen caerulescens caerulescens) and Ross’s geese (C. rossii) in the central Canadian Arctic - John Conkin; Ray T. Alisauskas (Polar Biology, 2017)

Effects of biological, economic and management factors on tuna and billfish stock status - Maite Pons; Trevor A Branch; Michael C Melnychuk; Olaf P Jensen; Jon Brodziak; Jean M Fromentin; Shelton J Harley; Alan C Haynie; Laurie T Kell; Mark N Maunder; Ana M Parma; Victor R Restrepo; et al. (Fish and Fisheries, 2017)
Commercial tunas and billfishes (swordfish, marlins and sailfish) provide considerable catches and income in both developed and developing countries. These stocks vary in status from lightly exploited to rebuilding to severely depleted. Previous studies suggested that this variability could result from differences in life‐history characteristics and economic incentives, but differences in exploitation histories and management measures also have a strong effect on current stock status. Although the status (biomass and fishing mortality rate) of major tuna and billfish stocks is well documented, the effect of these diverse factors on current stock status and the effect of management measures in rebuilding stocks have not been analysed at the global level. Here, we show that, particularly for tunas, stocks were more depleted if they had high commercial value, were long‐lived species, had small pre‐fishing biomass and were subject to intense fishing pressure for a long time. In addition, implementing and enforcing total allowable catches ( TAC s) had the strongest positive influence on rebuilding overfished tuna and billfish stocks. Other control rules such as minimum size regulations or seasonal closures were also important in reducing fishing pressure, but stocks under TAC implementations showed the fastest increase of biomass. Lessons learned from this study can be applied in managing large industrial fisheries around the world. In particular, tuna regional fisheries management organizations should consider the relative effectiveness of management measures observed in this study for rebuilding depleted large pelagic stocks.

Olfactory Mechanisms for Discovery of Odorants to Reduce Insect-Host Contact - Jonathan T. Clark; Anandasankar Ray (Journal of Chemical Ecology, 2016)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

Quantitative Study of As (V) and As (III) Interaction with Mangrove DNA by Molecular Fluorescence Spectroscopy - N. Majumder; C. Chowdhury; R. Ray; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2014)

Trading in snails: plant nurseries as transport hubs for non-native species - Elizabeth A. Bergey; Laura L. Figueroa; Charles M. Mather; Rebekah J. Martin; Eric J. Ray; Jobin T. Kurien; David R. Westrop; Phushewan Suriyawong (Biological Invasions, 2014)

Socio-cultural protection of endemic trees in humanised landscape - Rajasri Ray; M. D. Subash Chandran; T. V. Ramachandra (Biodiversity and Conservation, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Urban air-quality assessment and source apportionment studies for Bhubaneshwar, Odisha - Parth Sarathi Mahapatra; Sanak Ray; Namrata Das; Ayusman Mohanty; T. S. Ramulu; Trupti Das; G. Roy Chaudhury; S. N. Das (Theoretical and Applied Climatology, 2013)

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Nontidal ocean loading: amplitudes and potential effects in GPS height time series - T. van Dam; X. Collilieux; J. Wuite; Z. Altamimi; J. Ray (Journal of Geodesy, 2012)

Optimization of Culture Conditions for Production of Protease by Two Bacterial Strains, Bacillus licheniformis BF2 and Bacillus subtilis BH4 Isolated from the Digestive Tract of Bata, Labeo bata (Hamilton) - A. K. Ray; S. Mondal; T. Roy (Proceedings of the Zoological Society, 2012)

Water Dynamics in Fresh and Frozen Yeasted Dough - Simon M. Loveday; Victor T. Huang; David S. Reid; Ray J. Winger (Critical Reviews in Food Science and Nutrition, 2012)

Connectivity of prairie dog colonies in an altered landscape: inferences from analysis of microsatellite DNA variation - Loren C. Sackett; Todd B. Cross; Ryan T. Jones; Whitney C. Johnson; Kimberly Ballare; Chris Ray; Sharon K. Collinge; Andrew P. Martin (Conservation Genetics, 2012)

Rice Blast Management Through Host-Plant Resistance: Retrospect and Prospects - T. R. Sharma; A. K. Rai; S. K. Gupta; J. Vijayan; B. N. Devanna; S. Ray (Agricultural Research, 2012)

Movement and persistence by Ross’s Geese (Chen rossii) in Canada’s arctic - Ray T. Alisauskas; Kiel L. Drake; Jason H. Caswell; Dana K. Kellett (Journal of Ornithology, 2012)

Seasonal pulses of migratory prey and annual variation in small mammal abundance affect abundance and reproduction by arctic foxes - Gustaf Samelius; Ray T. Alisauskas; Serge Larivière (Polar Biology, 2011)

Delayed reward discounting and addictive behavior: a meta-analysis - James MacKillop; Michael T. Amlung; Lauren R. Few; Lara A. Ray; Lawrence H. Sweet; Marcus R. Munafò (Psychopharmacology, 2011)

Level of Heavy Metals in Some Edible Marine Fishes of Mangrove Dominated Tropical Estuarine Areas of Hooghly River, North East Coast of Bay of Bengal, India - T. K. De; M. De; S. Das; R. Ray; P. B. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Natural habitat change, commercial fishing, climate, and dispersal interact to restructure an Alaskan fish metacommunity - Peter A. H. Westley; Daniel E. Schindler; Thomas P. Quinn; Gregory T. Ruggerone; Ray Hilborn (Oecologia, 2010)

Movement patterns and habitat use of three declining littoral fish species in a north-temperate mesotrophic lake - Ray D. Valley; Michael D. Habrat; Eric D. Dibble; Melissa T. Drake (Hydrobiologia, 2010)

Antioxidant and oxidative stress responses of sojourners at high altitude in different climatic temperatures - Sanchari Sinha; Som Nath Singh; Mantu Saha; T. C. Kain; A. K. Tyagi; Uday Sankar Ray (International Journal of Biometeorology, 2010)

Carbon storage of bottomland hardwood afforestation in the Lower Mississippi Valley, USA - David T. Shoch; Gary Kaster; Aaron Hohl; Ray Souter (Wetlands, 2009)

Genome-wide analysis of Carica papaya reveals a small NBS resistance gene family - Brad W. Porter; Maya Paidi; Ray Ming; Maqsudul Alam; Wayne T. Nishijima; Yun J. Zhu (Molecular Genetics and Genomics, 2009)

Trace Element Concentrations in Blood of Nesting King Eiders in the Canadian Arctic - Mark Wayland; Ray T. Alisauskas; Dana K. Kellett; Katherine R. Mehl (Archives of Environmental Contamination and Toxicology, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Ecological correlates of duckling adoption among white-winged scoters Melanitta fusca: strategy, epiphenomenon, or combination? - Joshua J. Traylor; Ray T. Alisauskas; F. Patrick Kehoe (Behavioral Ecology and Sociobiology, 2008)

Anomalous harmonics in the spectra of GPS position estimates - J. Ray; Z. Altamimi; X. Collilieux; T. van Dam (GPS Solutions, 2008)

Does body size influence nest attendance? A comparison of Ross’s geese (Chen rossii) and the larger, sympatric lesser snow geese (C. caerulescens caerulescens) - Jón Einar Jónsson; Alan D. Afton; Ray T. Alisauskas (Journal of Ornithology, 2007)

Analysis of papaya BAC end sequences reveals first insights into the organization of a fruit tree genome - Chun Wan J. Lai; Qingyi Yu; Shaobin Hou; Rachel L. Skelton; Meghan R. Jones; Kanako L. T. Lewis; Jan Murray; Moriah Eustice; Peizhu Guan; Ricelle Agbayani; Paul H. Moore; Ray Ming; et al. (Molecular Genetics and Genomics, 2006)

Do geese fully develop brood patches? A histological analysis of lesser snow geese (Chen caerulescens caerulescens) and Ross’s geese (C. rossii) - Jón Einar Jónsson; Alan D. Afton; Dominique G. Homberger; William G. Henk; Ray T. Alisauskas (Journal of Comparative Physiology B, 2006)

Sex-biased costs in nest defence behaviours by lesser snow geese (Chen caerulescens): consequences of parental roles? - Gustaf Samelius; Ray T. Alisauskas (Behavioral Ecology and Sociobiology, 2006)

Tankyrase-1 overexpression reduces genotoxin-induced cell death by inhibiting PARP1 - Tsung-Yin J. Yeh; Juan I. Sbodio; M. T. Audrey Nguyen; Tobias N. Meyer; Ray M. Lee; Nai-Wen Chi (Molecular and Cellular Biochemistry, 2005)

The dynamics of landscape change and snow geese in mid‐continent North America - Kenneth F. Abraham; Robert L. Jefferies; Ray T. Alisauskas (Global Change Biology, 2005)
The Mid‐Continent Population of the lesser snow goose, which breeds in the eastern and central Canadian Arctic and sub‐Arctic, and winters in the southern United States and northern Mexico has increased 5–7% annually from the late 1960s to the mid‐1990s, largely because of increased survival in response to an agricultural food subsidy. The rise in numbers complements the increased use of nitrogen fertilizers and a corresponding rise in yields of rice, corn, and wheat along the flyways and on the wintering grounds. In sub‐Arctic migration areas and at Arctic breeding colonies, foraging by high numbers of birds has led to loss of coastal vegetation, adverse changes in soil properties and the establishment of an alternative stable state of exposed sediment, which can be detected with LANDSAT imagery. At a local scale, gosling growth, size and survival decreased in affected areas and other taxa have been adversely affected. The food subsidy on wintering and migration areas appears insufficient to meet reproductive demands as foraging in spring continues to occur on southern Hudson Bay staging and nesting areas. The recent introduction of liberal hunting regulations may reduce population size in the near term, but the revegetation of these coastal ecosystems will take decades to achieve. The present pattern of vegetation loss in these Arctic coastal systems is likely to continue in the forseeable future.

First report of Alternaria blight of Paulownia spp. - J. D. Ray; T. Burgess; N. Malajczuk; G. E. St J. Hardy (Australasian Plant Pathology, 2005)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Improvement in hydroxy fatty acid seed oil content and other traits from interspecific hybrids of three Lesquerella species: Lesquerella fendleri, L. pallida, and L. lindheimeri - David A. Dierig; Pernell M. Tomasi; Andrew M. Salywon; Dennis T. Ray (Euphytica, 2004)

Using GIS for siting artificial reefs—Data issues, problems and solutions: ‘Real World’ to ‘Real World’ - D. R. Green; S. T. Ray (Journal of Coastal Conservation, 2002)

Protein A-activated macrophages induce apoptosis in Ehrlich's ascites carcinoma through a nitric oxide-dependent pathway - S. Chattopadhyay; T. Das; G. Sa; P. K. Ray (Apoptosis, 2002)

Identification and classification of aromatic rices based on DNA fingerprinting - P. Ray Choudhury; S. Kohli; K. Srinivasan; T. Mohapatra; R.P. Sharma (Euphytica, 2001)

Foraging time and dietary intake by breeding Ross's and Lesser Snow Geese - Mark L. Gloutney; Ray T. Alisauskas; Alan D. Afton; Stuart M. Slattery (Oecologia, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Serum lipids, lipoproteins and sex-hormone binding globulin in breast cancer - A. Ray; S. L. Dayalu Naik; A. K. Bahadur; S. T. Pasha; R. S. Rautela; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

ES cell neural differentiation reveals a substantial number of novel ESTs - G. Bain; F.C. Mansergh; M.A. Wride; J.E. Hance; A. Isogawa; S.L. Rancourt; W.J. Ray; Y. Yoshimura; T. Tsuzuki; D.I. Gottlieb; D.E. Rancourt (Functional & Integrative Genomics, 2000)

Emplacement of Amba Dongar carbonatite-alkaline complex at Cretaceous/Tertiary boundary: Evidence from40Ar-39Ar chronology - Jyotiranjan S. Ray; Kanchan Pande; T. R. Venkatesan (Journal of Earth System Science, 2000)

Genetic engineering for abiotic stress resistance in crop plants - Jingxian Zhang; Natalya Y. Klueva; Z. Wang; Ray Wu; Tuan-Hua David Ho; Henry T. Nguyen (In Vitro Cellular & Developmental Biology - Plant, 2000)

Comparison of MPTP-induced changes in spontaneous neuronal discharge in the internal pallidal segment and in the substantia nigra pars reticulata in primates - T. Wichmann; Hagai Bergman; Philip A. Starr; Mahlon R. DeLong; Ray L. Watts; T. Subramanian (Experimental Brain Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Mechanisms of cytoplasmic pH regulation in alkaliphilic strains of Bacillus - T. A. Krulwich; M. Ito; Ray Gilmour; Arthur A. Guffanti (Extremophiles, 1997)

Transgenic sorghum plants obtained after microprojectile bombardment of immature inflorescences - Ana M. Casas; Andrzej K. Kononowicz; Theresa G. Haan; Lanying Zhang; Dwight T. Tomes; Ray A. Bressan; Paul M. Hasegawa (In Vitro Cellular & Developmental Biology - Plant, 1997)

Pleiotropic effect of the gene hairless on hepatotoxicity of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin in mice - J. B. Greig; J. E. Francis; S. J. E. Kay; T. Lister; D. E. Ray; A. A. Seawright; A. G. Smith (Archives of Toxicology, 1987)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Summary of papers presented at The Potato Conference held at the Western Regional Research Laboratory, October 17 and 18, 1949 - R. Kunkel; W. T. Penzer; Paul P. Logan; Ray Kueneman; W. A. Scott (American Journal of Potato Research, 1950)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)